1983
DOI: 10.1161/01.cir.68.4.763
|View full text |Cite
|
Sign up to set email alerts
|

Miscuffing: inappropriate blood pressure cuff application.

Abstract: For the accurate indirect measurement of blood pressure (BP), the American Heart Association (AHA) now recommends that cuff size should be based solely on limb circumference. We studied prevailing cuffing habits and compared them with newly revised AHA guidelines. Monitoring our staff's cuff applications, we found that "miscuffing" occurred in 65 (32%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 12 publications
(1 reference statement)
0
51
0
Order By: Relevance
“…142 The Cuff Studies of brachial blood pressure measurement highlight the importance of an appropriate cuff size to avoid inaccurate measurements. 143,144 Comparable information is not available on the size of the ankle cuff. If the same concept of cuff size used for the arm is applied to that of the ankle, the width of the cuff should be at least 40% of the limb circumference.…”
Section: Conditions For the Measurement Of The Abimentioning
confidence: 99%
“…142 The Cuff Studies of brachial blood pressure measurement highlight the importance of an appropriate cuff size to avoid inaccurate measurements. 143,144 Comparable information is not available on the size of the ankle cuff. If the same concept of cuff size used for the arm is applied to that of the ankle, the width of the cuff should be at least 40% of the limb circumference.…”
Section: Conditions For the Measurement Of The Abimentioning
confidence: 99%
“…Undercuffing has previously been shown to be the most common cuffing error resulting in an average increase of 8.5 mmHg systolic and 4.6 mmHg DBP 3 . However, our study found overcuffing to be the most common cuffing error resulting in significantly lower blood pressure measurements during triage compared to those obtained using the AHA method.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in blood pressure monitoring technique can result in significantly different readings. Numerous factors such as body position, arm position, inter-arm differences, cuff size, and cuff placement can affect the reading [3][4][5][6][7][8][9][10] . A study conducted recently on hypertensive patients compared usual blood pressure monitoring, ambulatory monitoring, and monitoring following the Canadian Hypertension Education Program protocol 11 .…”
Section: Introductionmentioning
confidence: 99%
“…82 More importantly, it has been demonstrated that the most frequent error in measuring blood pressure in the outpatient clinic is "miscuffing," with undercuffing large arms accounting for 84% of the "miscuffings." 83 The "ideal" cuff should have a bladder length that is 80% and a width that is at least 40% of arm circumference (a length-to-width ratio of 2:1). A recent study comparing intra-arterial and auscultatory blood pressure concluded that the error is minimized with a cuff width of 46% of the arm circumference.…”
Section: Cuff Sizementioning
confidence: 99%